Fragile Masculinity in Fair Play: Gender Dynamics in The Workplace - Agung, I Gusti Ayu Mahatma (International Journal of English and Applied Linguistics (IJEAL), 2026)
This study examined the representation of fragile masculinity in the film Fair Play by focusing on how masculine identity was constructed in a competitive professional setting. The study aimed to explore how rigid masculine expectations related to success, status, and authority shaped emotional and relational conflict. The analysis was guided by the Expectancy–Discrepancy–Threat Model of Masculine Identity. The model conceptualized masculinity as an identity that depended on external validation and became unstable when expectations were not met. A qualitative research design was applied, using the film as the primary data source. The findings showed that masculinity was initially constructed through strong workplace expectations that equated competence and ambition with masculine worth. These expectations were later disrupted by changes in professional hierarchy and performance failure, creating a discrepancy between masculine ideals and lived reality. As this discrepancy intensified, masculinity was perceived as being under threat, which triggered responses such as rigidity, blame, domination, and violence. The study demonstrated that these responses were shaped by environments that rewarded competition and showed low tolerance for vulnerability. Overall, the findings highlighted fragile masculinity as a relational and context-dependent process with significant emotional and social consequences.